Religion and governance - Chandra Muzaffar (Arah Publications, 2009)
This is perhaps one of the first books to explore in depth and detail the relationship between religion and governance. An attempt has been made to understand how the values and principles of nine diffrent spiritual and religious philosophies - Indigenous spirituality; Hinduism; Judaism; Buddhism; Confucianism; Christianity; Islam; Sikhism; and the Bahai faith - impact upon governance. What emerges from these nine discourses are a cluster of ideas which reveals that while their histories and theologies may be different, the various religions have many similarities in their common commitment to the dignity and the well-being of humanity. It is these parallels in their understanding of what constitute good governance which is the essence of this informative and insightful book.